Antioxidant potential of Eclipta alba, a traditional medicinal herb attenuates oxidative DNA damage in vitro - Purushothaman Ayyakkannu; Ganesh A; Meenatchi Packirisamy; Sundaram Ramalingam; Venkataramanan S (Smujo International, 2020)
Abstract. Purushothaman A, Ganesh A, Meenatchi P, Sundaram R, Venkataramanan. 2020. Antioxidant potential of Eclipta alba, a traditional medicinal herb attenuates oxidative DNA damage in vitro. Nusantara Bioscience 12: 73-78. The plant Eclipta alba (L.) Hassk. is an important plant used in the traditional Ayurvedic, Unani systems of holistic health and herbal medicine of the East. This study aimed to evaluate the antioxidant and DNA damage protection activities of ethanolic extract of E. alba. Quantitative analysis of total phenolic content (TPC) and identification of bioactive components using Gas Chromatography-Mass Spectroscopy (GC-MS) was performed to provide scientific basis for traditional usage of this plant. To investigate the antioxidant potential, extracts were tested for their capacity to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH·), hydrogen peroxide (H2O2) and Superoxide radicals (O2•-). DNA damage protective activity of ethanol extract of E. alba was checked on pBluescript M13+ plasmid DNA. The Plasmid DNA was oxidized with H2O2 + UV treatment in the absence and presence of different concentrations of E. alba extract (75, 150, and 300 ?g/mL). Electrophoresis was performed using 1% agarose at 40 V for 3 h in the presence of ethidium bromide. Gel was scanned on a Gel documentation system. Bands on the gels corresponding to supercoiled circular, circular relaxed, and linearized DNA were quantified. The results of preliminary phytochemical screening of E. alba extract showed the presence of flavonoids, saponins, steroids, terpenoids, and tannins. The extract was found to have rich phenolics content of 26.38 ± 2.45 milligram of gallic acid equivalents (mg GAE/g). The extract exhibited excellent antioxidant activities. GC-MS analysis of the extract confirmed the presence of major active principles. Furthermore, the extract significantly inhibited DNA damage induced by reactive oxygen species (ROS). Altogether, the results of current study revealed that E. alba is a potential source of antioxidants and provides pharmacological credibility to the ethnomedicinal use of this plant in traditional system of medicine, also justifying its therapeutic application in oxidative damage induced diseases such as cancer, diabetes, and neurological disorders.